2014
DOI: 10.3389/fnagi.2014.00338
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Enactment in Episodic Memory: A Pilot Virtual Reality Study with Young and Elderly Adults

Abstract: None of the previous studies on aging have tested the influence of action with respect to the degree of interaction with the environment (active or passive navigation) and the source of itinerary choice (self or externally imposed), on episodic memory (EM) encoding. The aim of this pilot study was to explore the influence of these factors on feature binding (the association between what, where, and when) in EM and on the subjective sense of remembering. Navigation in a virtual city was performed by 64 young an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
68
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(80 citation statements)
references
References 117 publications
(197 reference statements)
6
68
1
Order By: Relevance
“…Parsons and Rizzo (2008) reported positive correlations between a traditional word memory task and memory performance in a VR task in which younger adults had to recall a list of 10 items (e.g., a blue car) encoded while navigating a virtual city. Plancher, Nicolas, and Piolino (2008) and Jebara, Orriols, Zaoui, Berthoz, and Piolino (2014) found that older adults' performance on the recognition of items seen in a 2D VR car ride was positively correlated with performance on traditional recognition and executive tests, suggesting that the VR memory task may also reflect other cognitive capacities, such as executive processes.…”
mentioning
confidence: 99%
“…Parsons and Rizzo (2008) reported positive correlations between a traditional word memory task and memory performance in a VR task in which younger adults had to recall a list of 10 items (e.g., a blue car) encoded while navigating a virtual city. Plancher, Nicolas, and Piolino (2008) and Jebara, Orriols, Zaoui, Berthoz, and Piolino (2014) found that older adults' performance on the recognition of items seen in a 2D VR car ride was positively correlated with performance on traditional recognition and executive tests, suggesting that the VR memory task may also reflect other cognitive capacities, such as executive processes.…”
mentioning
confidence: 99%
“…In addition, future studies may opt to allow participants to determine their itinerary prior to physically exploring the rooms, or "on the go" rather than to instruct them to follow a specific route. Volition may increase the degree of interaction and enhance episodic memory (see Jebara et al, 2014). Further, technical limitations at the time of testing involved that online randomization (e.g., counterbalancing) of paintings would lead to novel and delayed rendering (because of differences in frame sizes of the paintings, resolution, light settings, etc.).…”
Section: Discussionmentioning
confidence: 99%
“…Participants navigated through a VR city via a steering wheel and pedals. Here, motoric control impaired item recognition (but not spatial memory) compared to conditions of passive viewing, which in turn performed worse than the volitional control condition (see : Jebara, Orriols, Zaoui, & Berthoz, & Piolino, 2014;Plancher, Barra, Orriols, & Piolino, 2013). Relevantly, Laurent, Ensslin, and Marí-Beffa (2016) provided a critical note, in that intensive motoric control may have distracted attention from encoding.…”
Section: Introductionmentioning
confidence: 88%
“…Being the self-locomotion the base of embodiment and grounding consequently episodic memory (Glenberg and Hayes, 2016) virtual promenades could compensate for the decrease of the spontaneous motion in elderly. Jebara et al (2014) investigated the effect of different types of virtual navigation on episodic memory in young and older adults. In a virtual environment designed as a city to be explored from inside a car, participants were asked to retrieve the events occurred with questions on “what,” “where,” and “when.” Participants were assigned to four experimental conditions: (1) in the passive condition participants were the passengers, with no possibility to interact with the environment; (2) in the itinerary control , participants chose the road but did not drive the car; (3) in the low navigation control , participants displayed the car on rails they could control with pedals without choosing the directions; (4) in the high navigation control , participants drove as in real life choosing also directions.…”
Section: Virtual Reality As a Tool To Improve Episodic Memory In The mentioning
confidence: 99%
“…The second limitation has to do with the cognitive load of the task. If the task is too demanding, this can have detrimental effects on the memory performance if attentional resources might split between complex motor tasks and memory task (Jebara et al, 2014). …”
Section: Virtual Reality As a Tool To Improve Episodic Memory In The mentioning
confidence: 99%